(untitled) (Orthodontic Journal of Nepal, 2015)
Orthodontists usually face problems with patients suffering from periodontal disease. The need for instituting periodontal treatment is of greater significance in such patients as chronic destructive periodontal diseases cause significant loss of supporting structures of the periodontium. A multidisciplinary approach should involve both orthodontist and periodontist to treat such patients and treatment progress should be evaluated periodically to implement a comprehensive treatment plan. The aim of this article is to highlight the contributing factors and procedures adjunctive to orthodontic treatment